IDENTIFICATION PROCESS OF MATERIAL RUBBER (BOKAR) PUBLIC INTO PTPN VII (PERSERO) UNIT PADANG PELAWI SELUMA REGENCY - Yesika Mei Nefftalia; Hasan Basri Daulay; Fitri Electrica D. Surawan (BPFP Faperta UNIB, 2015)
This research aimed to study of the material quality characteristics of rubber (bokar) in accordance with the SIR 20 and determine of the rubber material (bokar) public who go to the factory in accordance with the original supplier territory. The experiment was conducted in PTPN VII (Persero) Unit Padang Pelawi by collecting primary data and secondary data using survey and observation method, then analysis descriptive. The results showed that all though the rubber material (bokar) from public who go to PTPN VII (Persero) Unit Padang Pelawi doesn’t quality requirements of the Company and National Standardization Agency or BSN, while based on the dry rubber content or Kadar Karet Kering (KKK) of the rubber material (bokar) best is from Kaur.